Perbandingan Penerapan Algoritma A*, IDA*, Jump Point Search, dan PEA* P ada Permainan Pacman - Rosa Delima; Gregorius Titis Indrajaya; Abednego Kristiawan Takaredase; Ignatia Dhian E.K.R.; Antonius Rachmat C (Maranatha University Press, 2016)
Pathfinding is a way to find the shortest route between two points. There are several A* variant algorithms such as Iterative Deepening A* (IDA*) algorithm, Partial Expansion A* (PEA*), and Jump Point Search (JPS). In this research, the writer evaluates the performance of A*, IDA* algorithm, JPS, and PEA* algorithm. The algorithms are implemented in pacman game and the writer get the data by measuring visited nodes, and the route it takes. Based on the analysis of algorithms in a game, it concluded that the algorithms have the same path solution, but JPS algorithm has less visited nodes than A*, IDA*, and PEA*